2005
DOI: 10.1001/archpedi.159.11.1069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pectus Excavatum Deformity on Cardiorespiratory Fitness in Adolescent Boys

Abstract: As a group, boys with pectus excavatum deformity have lower endurance fitness than controls, and this is associated with reduced cardiac output and tidal volume responses to exercise. However, the wide variability of these measures makes it difficult to assign pectus deformity as a cause of exercise intolerance in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…This is similar to the results reported by Lawson et al [15], and suggests that the closed technique results in a significantly different long term outcome from the classical Ravitch technique. While the results are arguably modest, they do represent a normalization of function that would not be expected to occur without intervention [17].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is similar to the results reported by Lawson et al [15], and suggests that the closed technique results in a significantly different long term outcome from the classical Ravitch technique. While the results are arguably modest, they do represent a normalization of function that would not be expected to occur without intervention [17].…”
Section: Discussionmentioning
confidence: 70%
“…It is difficult to delineate the specific factors which may have led to this improvement; however, we would argue that it is due to a combination of improved efficiency of ventilation, and increased stroke volume (and secondarily cardiac output) at exercise. The perceived shortness of breath with intense exercise, which patients describe preoperatively is likely due to the reduced stroke volume at load caused by the pectus compression [6,17,19]. In normal subjects, maximal exercise capacity (and the shortness of breath which is the factor usually given as limiting by subjects) is directly correlated with oxygen delivery, which in turn relates primarily to cardiac output [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that patients with PE have impaired cardiorespiratory function compared to control group (3)(4)(5). The impact of these reduced physiological functions is not fully established; however, they may account for the presence and extent of physical limitations reported by patients.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of the deformity varies among patients, but the majority of patients complain of the poor cosmetic appearance caused by the deformed sternum (1,2). PE may also impair restrict chest wall movement and impair cardiorespiratory function (3)(4)(5). Patients report symptoms related to the deformity as exercise intolerance, shortness of breath, and weakness (2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…A robust medical and anaesthetic history should be taken in the pre-operative assessment clinic. Baseline cardiorespiratory functional capacity, and aerobic fitness is known to be diminished in patients with PE (18), and it has to be assessed before surgery. Allergies and intolerance are particularly important.…”
Section: Preoperative Anaesthetic Assessmentmentioning
confidence: 99%